Assessment of quality of treatment in insulin-treated patients with diabetes using a pre-filled insulin pen. The ORBITER Study Group - Albano, S.; Study Group, Orbiter (Acta Biomedica Atenei Parmensis, 2004)
International guidelines recommend that objectives for diabetes therapy include the reduction of complications associated with the disease, together with an improvement in the quality of psychosocial care and treatment satisfaction of people with diabetes. Purpose of the study was to assess the impact on the quality of treatment of replacing traditional syringe insulin injections with Novolet™ pre-filled insulin pen. The “Orbiter” observational study enrolled 1,622 insulin-treated diabetic patients from 91 Italian diabetes care centers. The survey was carried out by comparing the outcomes of the widely used Diabetes Treatment Satisfaction Questionnaire (DTSQ), at the time of enrolment (T0) and 30 days later (T+30). The following items were assessed: knowledge of the pathology, flexibility and ease of treatment, continuation and recommendation, hypoglycemia/hyperglycemia status and satisfaction. Replacement of the syringe with the Novolet ™ device produced a statistically significant improvement in all items assessed by the questionnaire. Scores were particularly relevant for the items “continuation” and “recommendation” and in subjects with an active working and social life. Elderly patients also indicated that the new device was easier to use and handle, although in a slightly less marked way. On the basis of the obtained results, Novolet™ pre-filled pen might represent a useful tool to improve quality of treatment in patients with insulin-treated diabetes leading to a better disease management and compliance to insulin-therapy.